Identification and quantitative evaluation of pores and throats of a tight sandstone reservoir (Upper Triassic Xujiahe Formation, Sichuan Basin, China). (June 2022) - Liu, Jingdong; Li, Lei; Zhang, Cunjian; Jiang, Youlu; Swennen, Rudy; Zhao, Chengjin; Hou, Shuai
Abstract: Pores and throats are the key parameters for determining the pore structure and fluid flow behavior in tight sandstone reservoirs. In this paper, pores and throats of the tight sandstone reservoir of the Upper Triassic Xujiahe Formation in the northern Sichuan Basin were investigated using classical petrography, scanning electron microscopy, and confocal laser scanning microscopy. In addition, a method of pore as well as throat identification and quantitatification using high-pressure mercury injection (HPMI) measurements was worked out. The results show that clay mineral-related pores are well developed in lithic sandstone and feldspathic lithic sandstone in addition to pores produced by dissolution of calcite cement and clastic grains. Intergranular pores are connected by lamellar, curved lamellar, and narrow pore throats. The pores and throats associated with intragranular dissolution and clay minerals are mostly tube shaped. The rapid-increasing and slow-increasing profiles of the mercury injection curves represent the dominance of pores and throats, respectively, allowing to differentiate pores and throats. Calculations show, in addition to fractured lithic sandstone, that has micron-sized pore–throat systems, the other lithic sandstones possess dominatly nano-sized pore–throat systems. In case of feldspathic lithic sandstones, micron-sized and nano-sized pore throat systems are equally important. In micron-sized pore throat dominated reservoirs, the pore volume is slightly larger than the throat volume, whereas for the nano-sized pore throat system, the pore volume is considerably larger than the throat volume. The key factors that are favorable for the formation of lithic sandstone pore throat systems are early calcite dissolution, lithic fragments dissolution, and early chlorite cementation. In contrast the key factors that are favorable for the formation of feldspathic lithic sandstone pore throat systems are dissolution of feldspars and lithic fragments. Highlights: A new method to distinguish pores and throats within tight sandstone reservoirs is proposed. Lithic and feldspathic lithic sandstone reservoirs host different pore and throat types. Pore volume is slightly larger than throat volume in the micron-size pore network. Pore volume is considerably larger than throat volume in the nano-size pore network. Compaction, cementation, and dissolution directly affected the development of pore throat systems.